Measuring customer-oriented product returns service performance. Issue 3 (12th August 2019) - Sajjanit, Chonlada; Rompho, Nopadol
Abstract : Purpose: The purpose of this paper is to conceptualise customer-oriented product returns service (COPRS) performance, and develop and validate its measure. Design/methodology/approach: This study uses qualitative consumer interviews and a quantitative survey to conceptualise, operationalise and validate the measure of COPRS performance. Findings: The findings indicate 12 components with 46 measurable items for COPRS performance, including assurance, compensation, convenience, empathy, employee empowerment, explanation, feedback, information availability, reliability, responsiveness, tangibles and timeliness. Research limitations/implications: The measure could facilitate future empirical studies in the product returns service area. Future research could apply the COPRS performance measure across industries or in different settings such as cross-cultural or other retailing contexts. Practical implications: Managers could evaluate their existing returns service performance in different key aspects based on the COPRS performance metrics and then improve their returns offerings accordingly. It also alerts practitioners to pay more attention to functional integration in designing returns service strategies to enhance customer satisfaction. Originality/value: The study is one of the first to develop a new measure that substantiates the notion of an integrated marketing and reverse logistics interface, which is an underrepresented body of knowledge in the marketing and operations management disciplines.